DAMPAK EKONOMI MASYARAKAT AKIBAT PENGALIHAN JALAN MINAS KE JALAN TOL PEKANB6-DUMAI - Khodijah, Siti; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
ABSTRACT This study aims to determine the economic impact on merchant households in terms of employment, income and social relations before and after the transfer of Jalan Minas to Jalan To Pekanbaru-Dumai. This research is a qualitative descriptive study which will be carried out in December 2022 in Minas District, Siak Regency, Riau. Data was collected through observation, interviews and documentation. Data analysis was carried out by data reduction analysis, data presentation, drawing conclusions. From the results of this study it can be concluded that before the transfer of the Minas road to the Pekanbaru-Dumai toll road, the household members of traders who were involved in economic activities were as many as 24 people but after that reduced to 11 people. In terms of income, there was a decline, where before the transfer of the Minas road to the Pekanbaru-Dumai toll road, the household income of traders at restaurants was relatively high, amounting to 5,800,000-6,000,000, but after that it was classified as medium, namely 3,8000,000-4,000,000. Previously, household income at coffee shops, workshops, barbershops and salons was classified as medium, namely 2,700,000- 3,850,000 but after that it was classified as low, namely 1,800,000-3,500,000. The social relations between the Minas people are also increasingly visible because many people no longer live in Minas due to work factors. Keywords: Merchant household members, work, income, social relations